Composite coal dust suppressant spraying system and application thereof
By using alkylphenol polyoxyethylene ether and modified xanthan gum to form a three-dimensional network structure in the spray system, the problem of the spray medium being difficult to wet hydrophobic coal dust was solved, achieving a highly efficient dust suppression effect in coal mines and reducing the occurrence of secondary dust.
Patent Information
- Application Number
- CN202511181576.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-07-08
- Filing Date
- 2025-08-22
- Publication Date
- 2025-12-26
AI Technical Summary
The existing spray medium, water, has a high surface tension and low viscosity, making it difficult to effectively wet and bind coal dust with strong hydrophobicity. This results in limited dust suppression capabilities, low dust suppression efficiency, and a tendency to generate secondary dust.
A composite coal dust suppressant spray system is adopted, including a spray unit and a dust suppressant solution. By adding alkylphenol polyoxyethylene ether and modified xanthan gum to form a three-dimensional network structure, the wettability, water retention and wind erosion resistance are improved. The nozzle is designed as a wide-angle solid type to enhance the spraying effect.
It significantly improves the dust suppression efficiency of spraying, with a dust suppression efficiency of over 80%, extends the dust suppression time, reduces secondary dust, and is suitable for the dust suppression needs of long-term coal mine operations.
Smart Images

Figure CN121197955A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of coal mine dust reduction, in particular to a mine dust control technology, and specifically relates to a composite coal dust suppressant spraying system and application thereof. BACKGROUND
[0002] In coal mining, coal dust pollution exists, and the existing dust suppressant has the problem of single function, such as only having wetting or binding function, low dust suppression efficiency, and easy secondary dust raising. The traditional water spraying is difficult to effectively wet the hydrophobic coal dust (contact angle of coking coal 61.6°±2.1°, measured according to GB / T30447-2013) due to the large surface tension (72.8mN / m, 25℃), and the evaporation rate reaches 0.42g / min in an environment of 30℃ and 40% relative humidity, resulting in short dust suppression time.
[0003] Although a single surfactant can reduce the surface tension, it has poor water retention, and a single binder has high viscosity but poor wetting. The traditional spraying dust reduction technology mainly changes the water droplet size and spraying range by optimizing the internal structure of the nozzle and adjusting the water and gas supply pressure to improve the dust reduction efficiency. However, due to the large surface tension and small viscosity of the spraying medium water, it is difficult to wet and bind the coal dust with strong surface hydrophobicity, and the spraying dust reduction capacity is limited.
[0004] In view of the above shortcomings, the coal dust suppressant spraying system needs to be improved to further improve the spraying dust reduction efficiency. SUMMARY
[0005] In view of the above-mentioned technical problems of the existing spraying medium water with large surface tension and small viscosity, which is difficult to wet and bind the coal dust with strong surface hydrophobicity, and the limited spraying dust reduction capacity, the technical solution adopted by the present application to solve the technical problems is: A composite coal dust suppressant spraying system, comprising a spraying unit and a dust suppressant solution, the spraying unit comprising a water storage tank, a high-pressure water pump and a wide-angle solid nozzle, the dust suppressant solution comprising at least alkylphenol polyoxyethylene ether and xanthan gum, and the dust suppressant solution being provided with a three-dimensional network structure for filling the voids of coal powder particles.
[0006] In view of the deficiencies of the prior art in improving the spraying dust reduction efficiency, the present application starts from the dust reduction mechanism, changes the spraying medium by adding materials to water to improve its wetting, binding, and condensation properties, and develops a composite dust suppressant that can form a three-dimensional network structure, thereby providing a composite dust suppressant spraying system with improved wetting, water retention, and wind erosion resistance, improving the efficiency of coal mine spraying dust reduction, and solving the problem of secondary dust raising.
[0007] The alkyl phenol polyoxyethylene ether as the wetting agent can significantly reduce the surface tension of water, improve the wetting performance of the dust suppressant on the coal dust, quickly spread on the surface of the coal dust through the solution, significantly reduce the contact angle, and enhance the ability to wrap or fill the gap of the coal dust, the xanthan gum as the binder has good cohesiveness and water retention, and the xanthan gum can cooperate to form a three-dimensional network structure and fill the gap of the coal dust particles, the three-dimensional network structure can enhance the anchoring effect of the solution on the coal dust, the dispersed coal dust particles are bonded into a group through viscous action, the relative movement between the particles is reduced, and then the cohesiveness and the wind erosion resistance of the dust suppressant on the coal dust can be enhanced.
[0008] For a single surfactant, although the surface tension can be reduced, the water retention is poor, when the dust suppressant is sprayed on the coal dust, the water in the dust suppressant will evaporate quickly, after the water evaporates, the coal dust that is originally wetted and bonded becomes dry and loose again, loses the constraint of the dust suppressant, and flies again, so that the dust suppression effect cannot be sustained, and the dust suppression time is greatly shortened. For mine dust control technology, the purpose of dust suppression is not only to make the coal dust temporarily stationary, but more importantly, to prevent the coal dust from flying for a certain period of time. If poor water retention makes the dust suppressant unable to maintain the wetting and bonding state of the coal dust for a long time, it is impossible to effectively suppress the secondary dust generated subsequently and the flying of the coal dust within a certain operation period, so that the long-time and stable dust suppression demand of coal mining and the like cannot be met.
[0009] Therefore, through the cooperation of the alkyl phenol polyoxyethylene ether and the xanthan gum, the composite solution of the present application can significantly reduce the evaporation speed, prolong the retention time of the solution on the surface of the coal dust, continuously exert the wetting and bonding effect, and be suitable for the dust suppression demand of long-time operation of the coal mine.
[0010] Further, the water storage tank of the present application is used for containing the dust suppressant solution, the dust suppressant solution based on the three-dimensional network structure is stably contained, so that the structure of the dust suppressant is prevented from being damaged, the wide-angle solid nozzle is used for spraying, and the high-pressure water pump is used for providing water pressure to improve the spraying effect. Specifically, the solid conical spray formed by the nozzle has higher droplet density than the hollow spray, and more opportunities for collision and adsorption with coal dust particles are provided in a unit volume, so as to improve the settling efficiency and wetting and bonding efficiency.
[0011] Further, in some embodiments of the present application, the aperture of the wide-angle solid nozzle is 1.5 mm, and the working pressure range is 0.5-1.5 MPa, the pressure range can make the dust suppressant based on the three-dimensional network structure uniformly dispersed, so as to improve the spraying effect.
[0012] Specifically, the composite dust suppressant solution contains xanthan gum and has a certain viscosity, so that the nozzle clogging problem caused by too small pore size can be avoided, and the 1.5 mm pore size can ensure sufficient flow and smooth spraying of the solution while avoiding the problem of too fast evaporation caused by too fine droplets. The flow is moderate at a working pressure of 0.5 MPa, which is suitable for preliminary wetting of the coal dust surface, and the working pressure of 1.5 MPa can enhance the penetration of the spray and cover a wider area.
[0013] Further, in some embodiments of the present application, the high-pressure water pump is connected to the wide-angle solid nozzle through a water delivery pipeline, and the working pressure is 1 MPa. At this pressure, the three-dimensional network structure can fully play a role, and the water delivery pipeline can stably deliver the composite dust suppressant solution containing xanthan gum and other high molecular components at a pressure of 1 MPa, avoiding the problem of reduced flow rate or uneven delivery caused by increased viscosity. The pressure of 1 MPa can drive the nozzle to produce a solid conical spray with a certain range and coverage, which can maintain good droplet density at a long distance, and the wide-angle solid nozzle with a 1.5 mm pore size can achieve good atomization effect of the dust suppressant solution. Specifically, under the pressure of 1 MPa, the dust suppressant based on the three-dimensional network structure has a settling time of ≤42 seconds for coking coal dust, and a 48-hour water loss rate of ≤55.92%, which reflects the improvement of the three-dimensional network structure in wettability and water retention.
[0014] Further, in some embodiments of the present application, the concentration of alkylphenol polyoxyethylene ether is in the range of 0.02%-0.08%, and in this concentration range, a stable dust suppressant solution can be formed. The concentration of xanthan gum is in the range of 0.03%-0.07%, which helps to build and stabilize the three-dimensional network structure. In some embodiments, the concentration of alkylphenol polyoxyethylene ether is 0.05%, and the concentration of xanthan gum is 0.05%. At this concentration, the three-dimensional network structure formed is stable and effective, and the surface tension of the dust suppressant solution is 31.3±0.5 mN / m, and the viscosity is ≥12 mPa·s (25℃). This surface tension and viscosity characteristics are related to the three-dimensional network structure, which is beneficial to improve the dust suppression performance.
[0015] Further, the xanthan gum is a modified xanthan gum with long-chain alkyl hydrophobic groups and metal ions.
[0016] Specifically, the ordinary xanthan gum needs a concentration greater than 0.1% to form a continuous three-dimensional network through intermolecular entanglement and hydrogen bonding, and if the concentration of xanthan gum is too low, an effective network cannot be formed. Since the synergistic effect of alkylphenol polyoxyethylene ether and xanthan gum is weak, the stability is insufficient, the entire dust suppressant system is prone to stratification and sedimentation, and the adhesion to coal powder is limited. If the concentration of alkylphenol polyoxyethylene ether is low and close to the critical micelle concentration, the reduction of the surface tension of the solution is limited, and if the surface of the coal powder is hydrophobic, the wettability is not improved enough, which makes it difficult for alkylphenol polyoxyethylene ether and xanthan gum to uniformly spread on the surface of the particles.
[0017] Without increasing the overall concentration of alkylphenol polyoxyethylene ether and xanthan gum, the modified xanthan gum with long-chain alkyl hydrophobic group and metal ions is used to further improve the three-dimensional network structure and the binding capacity to the surface of coal powder in this concentration range, and also reduces the environmental burden of the dust suppressant solution.
[0018] Specifically, the modified xanthan gum with long-chain alkyl hydrophobic group and metal ions comprises xanthan gum, dodecyl glycidyl ether, 2-aminoethyl pyridine, sodium hydroxide, hydrochloric acid, p-toluenesulfonic acid, deionized water, anhydrous ethanol, and calcium chloride.
[0019] The preparation method of the modified xanthan gum comprises the following steps: P1, adding sodium hydroxide to the prepared xanthan gum solution; Specifically, 10g of xanthan gum is weighed and added to 200mL of deionized water, stirred at 25℃ and 300rpm for about 2h to completely dissolve, forming a xanthan gum solution with a mass-volume ratio of 2%. 0.5g of sodium hydroxide is added to the xanthan gum solution, the pH is adjusted to 10-11, and the solution is stirred for 30min to deprotonate the hydroxyl groups of xanthan gum to form -O⁻ and enhance the reactivity.
[0020] P2, the dissolved dodecyl glycidyl ether-ethanol solution is added dropwise into the xanthan gum solution, heated to 50℃, stirred for 4h, and the reaction is terminated by adjusting the pH to 7.0 with hydrochloric acid solution to obtain a hydrophobically modified xanthan gum solution; Specifically, according to the molar ratio of xanthan gum repeat unit:dodecyl glycidyl ether=10:1, 3.2g of dodecyl glycidyl ether is weighed and dissolved in 50mL of anhydrous ethanol and stirred uniformly. The dodecyl glycidyl ether-ethanol solution is slowly added to the pretreated xanthan gum solution at a drop rate of 1mL / min, heated to 50℃, and stirred at a speed of 200rpm for 4h.
[0021] Specifically, the -O- of xanthan gum undergoes ring-opening etherification reaction with the epoxy group of glycidyl ether, covalently connecting the C12 alkyl chain to the side chain hydroxyl group of xanthan gum. The introduced long-chain alkyl group spontaneously aggregates due to the hydrophobic effect in aqueous solution, forming hydrophobic microdomains, and causing the xanthan gum molecules to transform from a dispersed state to a clustered aggregation, greatly shortening the intermolecular distance. After the reaction is completed, the pH is adjusted to 7.0 with 1 mol / L hydrochloric acid to terminate the reaction, and a hydrophobically modified xanthan gum solution is obtained.
[0022] P3, add p-toluenesulfonic acid to the hydrophobically modified xanthan gum solution, adjust the pH to 5.5-6.0, and drop 2-aminoethylpyridine solution into the hydrophobically modified xanthan gum solution, heat to 45°C, and stir for 6h, adjust the pH to 7.0 with 1 mol / L sodium hydroxide to obtain a hydrophobic-ligand double modified xanthan gum solution, and purify and dry to obtain a hydrophobic-ligand double modified xanthan gum powder; Specifically, 0.3 g of p-toluenesulfonic acid is added as a catalyst to the hydrophobically modified xanthan gum solution, stirred for 10 min, and the pH is adjusted to 5.5-6.0 to promote amidation under acidic conditions. According to the molar ratio of xanthan gum repeating unit: 2-aminoethylpyridine = 20:1, 1.1 g of 2-aminoethylpyridine is weighed and dissolved in 30 mL of deionized water, and slowly dropped into the hydrophobically modified xanthan gum solution at a drop rate of 0.5 mL / min, heated to 45°C, and stirred at a rotation speed of 150 rpm for 6h. The carboxyl group of the side chain of xanthan gum and the amino group of 2-aminoethylpyridine undergo amidation reaction under acidic conditions, thereby connecting the pyridyl group to the side chain.
[0023] After the reaction is completed, the pH is adjusted to 7.0 with 1 mol / L sodium hydroxide to obtain a hydrophobic-ligand double modified xanthan gum solution, the hydrophobic-ligand double modified xanthan gum solution is transferred into a dialysis bag with a molecular weight cut-off of 8000-14000 Da, and the dialysis bag is dialyzed against deionized water for 48h, with water being replaced every 6h to remove unreacted reagents and small molecular impurities. The dialyzed solution is freeze-dried at -50°C, a vacuum degree of 10 Pa for 24h to obtain a hydrophobic-ligand double modified xanthan gum powder, which is sealed and stored.
[0024] P4, according to the mass ratio of hydrophobic-ligand double modified xanthan gum powder: Ca 2+ =100:1, a calcium chloride solution is added to the prepared hydrophobic-ligand double modified xanthan gum solution, and stirred to obtain a long-chain alkyl hydrophobic group and metal ion modified xanthan gum.
[0025] Specifically, the hydrophobic-coordination double modified xanthan gum powder is weighed, prepared into an aqueous solution, dissolved by stirring at 25 DEG C for 1 h, calcium chloride solution is added in a mass ratio of hydrophobic-coordination double modified xanthan gum powder:Ca 2+ =100:1, stirred for 10 min, Ca 2+ forms a coordination bond with the pyridine group of the hydrophobic-coordination double modified xanthan gum, crosslinking nodes are formed among the hydrophobic aggregated molecules, and a continuous network is constructed, and the above solution is subjected to the steps of dialysis and freeze-drying to obtain the modified xanthan gum powder of long-chain alkyl hydrophobic groups and metal ions.
[0026] Specifically, the hydrophobic-coordination synergistically modified xanthan gum can form a stable three-dimensional network at a low concentration of 0.03%-0.07% through the dual effects of shortening the intermolecular distance by hydrophobic aggregation and fixing the structure by coordination crosslinking, and can meet the gap filling demand of coal dust particles.
[0027] Further, in some embodiments of the present application, the dust suppressant solution further comprises a first additive for improving dust suppression efficiency and a second additive for improving solution stability, the concentration of the first additive ranges from 0.01% to 0.05%, and the concentration of the second additive ranges from 0.01% to 0.05%.
[0028] Further, the first additive comprises chitosan quaternary ammonium salt, silane coupling agent and layered montmorillonite, and the second additive comprises carrageenan, dispersant and pH value regulator.
[0029] Specifically, the chitosan quaternary ammonium salt is hydroxypropyl trimethyl ammonium chloride chitosan, the silane coupling agent is silane coupling agent KH560, the layered montmorillonite is coconut quaternary ammonium salt modified layered montmorillonite, the carrageenan is iota-carrageenan, the dispersant is sodium polyacrylate and polysorbate 80, and the pH value regulator is a citric acid-sodium citrate buffer system.
[0030] The hydroxypropyl trimethyl ammonium chloride chitosan has a high density of quaternary ammonium salt positive charge groups introduced on the molecular chain, can effectively adsorb negatively charged coal dust particles, improve the sedimentation efficiency, and improve the water solubility, in the solution, the chitosan quaternary ammonium salt can form a flexible film covering the surface of the dust particles, reduce the electrostatic repulsion between the particles, enhance the agglomeration effect, and inhibit the dust raising, has a certain antibacterial ability, can prolong the storage stability of the dust suppressant, and further, the hydroxypropyl trimethyl ammonium chloride chitosan is biodegradable, can reduce the influence of the dust suppressant on the environment.
[0031] The silane coupling agent KH560 has a hydrolysable siloxane group at one end, which can be hydrolyzed into a silanol group-Si(OH)3, and reacts with a silicon / oxygen functional group. The other end is an epoxy group, which can provide certain hydrophobicity and weather resistance. During preparation, the silane coupling agent KH560 can be combined with the siloxane skeleton of montmorillonite through hydrolysis and condensation, and its epoxy group can chemically react with the hydroxyl or amino group of the quaternary ammonium salt of chitosan to form covalent bonds or hydrogen bonds, thereby improving the interfacial compatibility between montmorillonite and xanthan gum, chitosan, preventing montmorillonite from agglomerating in the matrix, and improving its dispersibility.
[0032] The coconut quaternary ammonium salt modified layered montmorillonite has long-chain alkyl inserted between the layers, and the surface becomes hydrophobic-cationic. The interlayer hydrophobic chain can synergize with other hydrophobic groups. The 1-5 μm layered structure of the modified montmorillonite can be inserted into the three-dimensional network of the modified xanthan gum, forming a network-montmorillonite interpenetrating structure through hydrophobic interaction, making the network pore size of 5-10 μm more stable, and preventing deformation when filling the 5-20 μm gap of coal dust, thereby improving the physical barrier effect. The quaternary ammonium cation on the surface of the coconut quaternary ammonium salt modified layered montmorillonite can be electrostatically adsorbed to the negative sites of coal dust, enhancing the dust capture ability of the dust suppressant. At the same time, the layered structure can physically wrap the coal dust particles between the layers, and the cationic adsorption forms a combination of electrostatic and physical fixation. The rigid structure of the montmorillonite layer can enhance the mechanical strength of the dust suppressant network, resist external forces such as wind and rain, and its hydrophobic surface can reduce the penetration of water molecules into the network, preventing the network from swelling and loosening due to water absorption, and improving the stability in a humid environment.
[0033] The sodium polyacrylate is an anionic polymer, and the carboxylate on its molecular chain is negatively charged after dissociation in water, which can prevent the agglomeration of negatively charged coal dust particles through electrostatic repulsion. In a low ionic strength system, sodium polyacrylate and hydroxypropyltrimethylammonium chloride chitosan form a complementary adsorption network through electrostatic interaction, enhancing the capture ability of coal dust. At the same time, sodium polyacrylate has little interference with the three-dimensional hydrogen bond network of xanthan gum, and the two can synergistically stabilize the dust suppressant system. In addition, sodium polyacrylate can compete with chitosan for Ca 2+ Inhibits the ionic crosslinking gelation of carrageenan.
[0034] The hydrophobic chain of polysorbate 80 combines with the hydrophobic region of coconut oil-based montmorillonite, and the hydrophilic polyoxyethylene chain forms a hydration layer, which is stably dispersed through steric hindrance, and cooperates with alkylphenol polyoxyethylene ether to reduce surface tension and enhance the wettability of coal dust, avoiding charge interference with other components.
[0035] ι-carrageenan, in the presence of Ca 2+The presence of the hydroxyl groups on the molecular chains of the xanthan gum can form hydrogen bonding with the xanthan gum, thereby further enhancing the stability and viscoelasticity of the network structure. The competition between the ι-carrageenan and the xanthan gum for hydration is not easy to occur, but instead, a stable composite network structure can be formed through non-covalent interaction, showing a good synergistic thickening effect.
[0036] Specifically, the preparation method of the coconut-based quaternary ammonium salt modified layered montmorillonite comprises the following steps: Q1, ultrasonic treatment and dispersion of the layered sodium-based montmorillonite into deionized water, standing for 2 hours to remove suspended impurities, filtering and drying at 80°C for 12 hours to obtain purified montmorillonite; Specifically, 5g of layered sodium-based montmorillonite is dispersed in 200mL of deionized water, and ultrasonic treatment is carried out at a power of 300W for 30min to completely expand, and after standing, the Ca 2+ , Mg 2+ and other metal ions in the montmorillonite are removed, which can improve the ion exchange efficiency. Further, the cation exchange capacity of the layered sodium-based montmorillonite is 80-120mmol / 100g, and the particle size is more than 200 mesh.
[0037] Q2, dissolve the coconut-based quaternary ammonium salt in hot water and stir until transparent; Specifically, 2.5g of coconut-based trimethylammonium chloride is dissolved in 50mL of 60°C hot water, and stirred until transparent. This temperature can avoid exceeding the melting point of the quaternary ammonium salt and prevent the ring-opening of the epoxy group.
[0038] Q3, add the purified montmorillonite to 1.5L of deionized water, ultrasonic dispersion for 30min to form a suspension, adjust the pH to 6-7, slowly add the coconut-based quaternary ammonium salt solution, mechanical stirring at 300rpm at 60°C for 4h, and keep the pH stable. Adjusting the pH to 6-7 can prevent the aggregation of the montmorillonite layers, specifically, the amount of quaternary ammonium salt: the cation exchange capacity of the layered sodium-based montmorillonite = 1.5:1, when the cation exchange capacity of the layered sodium-based montmorillonite is 100mmol / 100g, 1.5g of quaternary ammonium salt is added per 1g of layered sodium-based montmorillonite, further, the reaction temperature at 60°C can balance the activity and stability of the quaternary ammonium salt, and the stirring speed at 300rpm can promote the dispersion and ion exchange of the montmorillonite.
[0039] Q4, centrifuge at 5000rpm for 10min to collect the precipitate, wash with 1:1 volume ratio of ethanol-water solution for 3 times to remove free quaternary ammonium salt, and by removing the unreacted quaternary ammonium salt and by-product sodium chloride, the stability of the dust suppressant can be avoided. Through 60°C vacuum drying for 24h, grinding through a 200 mesh sieve, the coconut-based quaternary ammonium salt modified layered montmorillonite is obtained.
[0040] Further, in some embodiments of the present application, the spray angle of the wide-angle solid nozzle is 120°, and the droplet size range is 50-200 μm, which is conducive to uniform coverage of the dust suppressant based on the three-dimensional network structure.
[0041] Further, in some embodiments of the present application, the installation height of the wide-angle solid nozzle is 0.5-1.5 m away from the dust source, and the spray coverage area is ≥2 m², which can ensure the effective range of the three-dimensional network structure containing dust suppressant. Specifically, when the coverage area is ≥2 m², a single nozzle can effectively control the dust diffusion in a larger range and improve the capture efficiency of suspended particles. The installation height of 0.5-1.5 m away from the dust source can form a mist curtain barrier before the coal dust has been generated and has not yet spread extensively, directly covering and suppressing the dust source, reducing the total amount of coal dust spreading to the working space, and reducing the degree of dust pollution from the source, avoiding the problem of mist droplets being blown away by air flow and attenuating in concentration before reaching the dust source due to the installation of the nozzle being too far away, and also avoiding the local coal dust being raised again or the equipment being disturbed due to the spray rebounding due to being too close. Additionally, within the height range of 0.5-1.5 m, the time for the mist droplets to be sprayed from the nozzle to contact the dust source is moderate, neither affecting the wettability due to the mist droplets not being fully atomized due to being too close, nor causing excessive evaporation of the mist droplets due to being too far away.
[0042] Further, in some embodiments of the present application, the three-dimensional network structure has pores with a pore size of 5-10 μm, which can effectively fill the voids of coal particles and enhance particle agglomeration.
[0043] Further, in some embodiments of the present application, the dust suppressant solution is prepared at a temperature range of 20-30 °C and a stirring speed of 300-500 r / min to obtain a three-dimensional network structure.
[0044] Specifically, the preparation method of the dust suppressant solution comprises the following steps, S1, after the layered montmorillonite is mixed with part of the dispersant, it is mixed and stirred with the modified xanthan gum to obtain a first mixed solution; Specifically, the weighed polysorbate 80 is added to the deionized water and stirred for 5 minutes until completely dissolved, and the coconut oil-based quaternary ammonium salt modified montmorillonite is slowly added, the stirring speed is increased to 500 rpm and stirred for 20 minutes, the agglomerates are dispersed by shearing, the hydrophobic ester chain of polysorbate 80 is combined with the coconut oil group of montmorillonite, and the hydrophilic EO chain is stretched outward to form a hydration layer to prevent the lamellar stacking. At this time, the prepared modified xanthan gum solution is slowly added, the stirring speed is reduced to 300 rpm and stirred for 30 minutes, and the low stirring speed avoids bubbles, allowing the molecular chain to fully stretch, until the solution is slightly viscous, and the long-chain alkyl hydrophobic group of the modified xanthan gum is associated with the metal ions in the configuration process by twelve alkyl hydrophobic association and Ca 2+2-Aminoethylpyridine coordinates to initially form a three-dimensional network, thereby forming a skeletal support.
[0045] S2. Add carrageenan to the first mixture and stir. Add silane coupling agent and stir to obtain the second mixture. Dissolve ι-carrageenan in deionized water and stir for 10 minutes until dissolved. Slowly add the solution dropwise to the first mixture and stir at 300 rpm for 20 minutes. The galactose backbone of carrageenan and the glucose backbone of xanthan gum are linked by hydrogen bonds. -SO3 - The polar interaction with the -OH group of xanthan gum leads to increased network viscosity, enhanced elasticity, and a shear recovery rate >80%. The silane coupling agent KH560 is dissolved in anhydrous ethanol and slowly added dropwise to a first mixture containing carrageenan. The mixture is stirred at 300 rpm for 20 minutes. The epoxy groups of the silane coupling agent KH560 react with the hydroxyl groups of xanthan gum and carrageenan, and the siloxane chains combine with the silanol groups of montmorillonite to form a polysaccharide-coupling agent-montmorillonite bridging structure, thereby enhancing the overall integrity of the network.
[0046] S3. Add the remaining dispersant to the second mixture, then add chitosan quaternary ammonium salt and mix to obtain the third mixture; dissolve sodium polyacrylate in deionized water, stir for 10 minutes until transparent, slowly add to the second mixture, and stir at 300 rpm for 20 minutes to obtain the -COO group of sodium polyacrylate. - It forms hydrogen bonds with the -OH group of xanthan gum, and simultaneously forms hydrogen bonds with the -COO group of xanthan gum through electrostatic repulsion. - Expanding the network pores enhances the filling effect on coal dust. Hydroxypropyltrimethylammonium chloride chitosan is dissolved in deionized water and slowly added to a second mixture containing sodium polyacrylate. The mixture is stirred at 300 rpm for 30 minutes. At this point, the second mixture already contains a network of xanthan gum, carrageenan, and sodium polyacrylate, which buffers the cationic nature of chitosan and prevents direct flocculation. The -N... + (CH3)3 is uniformly distributed in the network and can be exposed on the surface to adsorb negative ion coal dust.
[0047] S4. Add alkylphenol polyoxyethylene ether to the third mixture, adjust the pH to 6.5-8.0, add deionized water, and stir evenly to obtain a dust suppressant solution.
[0048] Specifically, alkylphenol polyoxyethylene ether OP-10 was dissolved in deionized water and stirred for 5 minutes until transparent. This solution was then added to the third mixture and stirred at 300 rpm for 20 minutes. The octyl group of alkylphenol polyoxyethylene ether OP-10 forms hydrophobic microdomains with the dodecyl group of xanthan gum and the coconut oil group of montmorillonite. Its EO chain synergistically reduces surface tension with the EO chain of polysorbate 80. Citric acid or sodium citrate was slowly added, and the pH was monitored to 6.5-8.0 using a pH meter to ensure the Ca... 2+The coordination stability and cationic property of chitosan are used to prepare the dust suppressant solution by adding deionized water to a total volume of 1000 mL under stirring at 300 rpm for 15 minutes, eliminating local concentration difference under stirring at 500 rpm for 10 minutes, removing air bubbles under standing for 30 minutes after monitoring the pH value by a pH meter, and obtaining the dust suppressant solution.
[0049] Specifically, the coal dust exists in the form of a particle accumulation body formed by mutual stacking of numerous micron-level coal dust particles, and the inter-particle gap is mainly less than 75 μm, especially the flying coal dust has the highest proportion in the gap of 5-20 μm, and the particle surface contains a hydrophobic region, a negative charge site, and an oxygen-containing functional group. The three-dimensional network structure of the dust suppressant solution with a pore size of 5-10 μm penetrates and fills the gap between the coal dust particles, forms a physical blockage, prevents the airflow from carrying the coal dust through the gap, the functional groups in the dust suppressant are combined with the sites on the surface of the coal dust particles, the network filled in the gap is anchored with the coal dust particles, and the network is prevented from being washed away by the airflow. The 1-5 μm coconut-based montmorillonite in the network is inserted therein, the network forms a continuous skeleton in the gap by mutual entanglement of the dodecyl and coconut-based hydrophobic chains, and the channel of the coal dust is blocked. Meanwhile, the elastic katalgum of the network can adapt to the irregular shape of the gap, and ensures that the filling is compact. The octyl hydrophobic groups of the dodecyl and alkyl phenol polyoxyethylene ether OP-10 in the network spontaneously migrate to the hydrophobic region of the carbon skeleton on the surface of the coal dust, are combined with the surface of the coal dust through hydrophobic interaction and van der Waals force, connect the network filled in the gap with the surrounding coal dust particles, and prevent the network from falling off from the gap.
[0050] Specifically, the cation in the dust suppressant, the -N + The quaternary ammonium group of the modified montmorillonite will be electrostatically attracted to the negatively charged surface of the coal dust particles, will pull the coal dust particles around the gap to the dust suppressant network filled in the gap, will make the particles closely adhere to the network, will reduce the loose space in the gap, and the long-chain structure of chitosan can simultaneously adsorb multiple coal dust particles, will bond multiple coal dust particles around the network, and will strengthen the integrity of the gap filling.
[0051] Specifically, one end of the silane coupling agent KH560 is covalently combined with the dust suppressant network filled in the gap, and the other end is covalently combined with the oxygen-containing functional group of the coal dust particle on the gap wall, a chemical bridge is erected between the network in the gap and the coal dust particle on the gap wall, the network is prevented from peeling off from the gap, the Si-O-Si bond and ether bond formed by the coupling agent on the surface of the coal dust can fix the hydrophobic network and cationic components of the dust suppressant on the surface of the coal dust, and the dust suppressant is prevented from falling off from the surface of the coal dust.
[0052] Another object of the present application is to provide an application of the composite coal dust dust suppressant spraying system, comprising the composite coal dust dust suppressant spraying system as described above, and the system is applied to coal mine dust reduction.
[0053] Specifically, after spraying water on the surface of coal, the water on the surface of coal is surface adsorbed water and capillary water, and an air film is formed between the water and the coal. Because the coal is hydrophobic, the water and the coal do not adhere to each other. Therefore, the sprayed water evaporates quickly, and the dust suppression effect disappears quickly. The composite dust suppressant is sprayed on the surface of the coal, which ensures the wettability, permeability and adhesion between the coal particles. Part of the effective components contained in the composite dust suppressant is used to wet the coal, and the other part is agglomerated to form a three-dimensional network structure, and penetrates and fills the gaps of the coal particles to form a solidified layer with close arrangement. The xanthan gum reduces the interfacial tension while retaining the good water retention of polysaccharides. Therefore, the composite dust suppressant can solidify the coal powder and enhance the particle agglomeration. In addition, the presence of xanthan gum makes the solidified layer retain a certain amount of moisture, thereby preventing the cracking of the dry solidified layer, reducing the evaporation rate of water, and enhancing the dust suppression effect.
[0054] The three-dimensional network structure enables the dust suppressant to have excellent wettability, water retention, adhesion and wind erosion resistance. Among them, the alkylphenol polyoxyethylene ether of the dust suppressant can reduce the interfacial tension, improve the wettability of the dust suppressant to coal dust, and the xanthan gum of the dust suppressant can effectively retain water, enhance water retention and adhesion. Experimental verification shows that under a water pressure of 1 MPa, the dust suppression efficiency of the dust suppressant is improved by 20% compared with the traditional system, and the water retention for 48 hours is better than that of the traditional system by 30%.
[0055] Through surface tension, contact angle and sedimentation experiments, the prepared dust suppressant has a pH value close to neutral and is environmentally friendly and non-polluting. The spray dust suppression experiment shows that under a working pressure of 0.5-1.5 MPa, the dust suppression efficiency can reach more than 80% with the spray system, which is significantly higher than that of water alone, and in some embodiments, it can reach more than 90%, which can effectively reduce dust in coal mine and other dusty environments, and is especially suitable for dust control in coal mine tunnels and coal storage yards.
[0056] Specifically, the dust suppressant based on the three-dimensional network structure forms a solidified layer on the surface of the coal dust after spraying, and the wind erosion resistance meets: under a wind speed of 10 m / s and a blowing time of 5 minutes, the mass loss of the coal sample is ≤0.36 g under the condition of an initial coal sample of 10 g. Thanks to the enhanced adhesion and stability of the three-dimensional network structure, the mass loss of the coal sample is ≤0.36 g.
[0057] In some embodiments, the effective component in the dust suppressant solution reduces the surface tension to 31.3 mN / m (a decrease of 56%), reduces the contact angle of the coking coal to 15.09°, and increases the viscosity to >12 mPa·s, and the three-dimensional network structure formed has a water retention of 23% better than pure water after 48 hours; in some embodiments, the effective component in the dust suppressant solution reduces the surface tension to 30.7 mN / m, reduces the contact angle of the coking coal to 14.87°, and after spraying, the mass loss of the coal sample under a wind speed of 10 m / s is only 0.24-0.36 g (more than 90% less than pure water), and under a water pressure of 1 MPa, the dust suppression efficiency reaches 83.82% (an increase of 9.75% compared with pure water), which balances efficiency and economy.
[0058] The beneficial effects of the present application are as follows: 1. The present application improves the wettability, adhesion, and coagulation properties of water by adding materials to water, and develops a composite dust suppressant capable of forming a three-dimensional network structure, and provides a composite dust suppressant spraying system that synergistically improves wettability, water retention, and wind erosion resistance, thereby improving the efficiency of coal mine spraying dust suppression and solving the problem of secondary dust.
[0059] 2. The dust suppressant of the present application, in combination with the spraying system, has a dust suppression efficiency of more than 80%, which is significantly higher than that of pure water alone, and can effectively reduce dust in coal mine and other dusty environments, and is particularly suitable for dust control in coal mine tunnels and coal storage yards. BRIEF DESCRIPTION OF DRAWINGS
[0060] Figure 1 The figure is a schematic diagram of the spraying system of the present application. DETAILED DESCRIPTION
[0061] The embodiments of the present application will be described in detail below with reference to the accompanying drawings. The described embodiments are only a part of the embodiments of the present application, not all. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0062] In order to make those skilled in the art more clearly understand the technical solutions described in the present application, the following examples are given for illustration. The raw materials, reagents or devices used in the following embodiments, unless otherwise specified, can be obtained from conventional commercial channels or by known methods.
[0063] A composite coal dust suppressant spraying system, comprising a spraying unit and a dust suppressant solution, the spraying unit comprising a water storage tank 1, a high-pressure water pump 2, and a wide-angle solid nozzle 3, the dust suppressant solution comprising at least alkylphenol polyoxyethylene ether and xanthan gum, and the dust suppressant solution being provided with a three-dimensional network structure for filling the voids of coal particles.
[0064] The aperture of the wide-angle solid nozzle 3 is 1.5 mm, and the working pressure range is 0.5-1.5 MPa.
[0065] The high-pressure water pump 2 is connected with the wide-angle solid nozzle 3 through the water delivery pipeline 4, and the working pressure is 1 MPa.
[0066] The alkylphenol polyoxyethylene ether concentration range is 0.02%-0.08%, and the xanthan gum concentration range is 0.03%-0.07%. The alkylphenol polyoxyethylene ether is OP-10, and the xanthan gum is a modified xanthan gum with long-chain alkyl hydrophobic groups and metal ions, which includes xanthan gum, dodecyl glycidyl ether, 2-aminoethyl pyridine, sodium hydroxide, hydrochloric acid, p-toluenesulfonic acid, deionized water, anhydrous ethanol, and calcium chloride.
[0067] The preparation method of the modified xanthan gum includes the following steps: P1, adding sodium hydroxide to the prepared xanthan gum solution; Specifically, 10 g of xanthan gum is weighed and added to 200 mL of deionized water, stirred at 25°C and 300 rpm for about 2 h until completely dissolved, 0.5 g of sodium hydroxide is added to the xanthan gum solution, the pH is adjusted to 10-11, and stirring is performed for 30 min.
[0068] P2, according to the molar ratio of xanthan gum repeating units:dodecyl glycidyl ether=10:1, 3.2 g of dodecyl glycidyl ether is weighed and dissolved in 50 mL of anhydrous ethanol, and stirred uniformly. The dodecyl glycidyl ether-ethanol solution is slowly added to the pretreated xanthan gum solution at a drop rate of 1 mL / min, the temperature is raised to 50°C, and the stirring speed is 200 rpm for 4 h of reaction. After the reaction is completed, 1 mol / L hydrochloric acid is used to adjust the pH to 7.0 to terminate the reaction, and a hydrophobically modified xanthan gum solution is obtained.
[0069] P3, 0.3 g of p-toluenesulfonic acid is added to the hydrophobically modified xanthan gum solution as a catalyst, stirring is performed for 10 min, the pH is adjusted to 5.5-6.0, according to the molar ratio of xanthan gum repeating units:2-aminoethyl pyridine=20:1, 1.1 g of 2-aminoethyl pyridine is weighed and dissolved in 30 mL of deionized water, and slowly added to the hydrophobically modified xanthan gum solution at a drop rate of 0.5 mL / min, the temperature is raised to 45°C, and the stirring speed is 150 rpm for 6 h of reaction. After the reaction is completed, 1 mol / L sodium hydroxide is used to adjust the pH to 7.0, a hydrophobically-coordinated double-modified xanthan gum solution is obtained, the hydrophobically-coordinated double-modified xanthan gum solution is transferred to a dialysis bag with a molecular weight cut-off of 8000-14000 Da, and the dialysis bag is dialyzed against deionized water for 48 h, with water being changed every 6 h to remove unreacted reagents and small molecular impurities. After dialysis, the solution is subjected to freeze-drying at -50°C, a vacuum degree of 10 Pa, and for 24 h to obtain a hydrophobically-coordinated double-modified xanthan gum powder, which is sealed and stored; P4, the mass ratio of hydrophobic-coordination double modified xanthan gum powder: Ca²⁺ = 100:1, add calcium chloride solution to the prepared hydrophobic-coordination double modified xanthan gum solution, stir for 10 min, and obtain the modified xanthan gum solution of long-chain alkyl hydrophobic group and metal ion. The above solution is transferred into a dialysis bag with a molecular weight cut-off of 8000-14000 Da, and dialyzed with deionized water for 48 h, and the water is changed every 6 h to remove unreacted reagents and small molecular impurities. The solution after dialysis is freeze-dried at -50℃, vacuum degree 10 Pa for 24 h to obtain long-chain alkyl hydrophobic group and metal ion modified xanthan gum powder.
[0070] The dust suppressant solution also includes a first auxiliary agent for improving dust suppression efficiency, a second auxiliary agent for improving solution stability, the concentration of the first auxiliary agent ranges from 0.01% to 0.05%, and the concentration of the second auxiliary agent ranges from 0.01% to 0.05%.
[0071] Further, the first auxiliary agent includes chitosan quaternary ammonium salt, silane coupling agent, and layered montmorillonite, and the second auxiliary agent includes iota carrageenan, dispersant, and pH value regulator.
[0072] The concentration ranges of the first auxiliary agent include 0.002%-0.02% of chitosan quaternary ammonium salt, 0.005%-0.03% of silane coupling agent, and 0.002%-0.02% of layered montmorillonite, and the concentration ranges of the second auxiliary agent include 0.005%-0.03% of iota carrageenan, 0.002%-0.02% of dispersant, and 0.002%-0.02% of pH value regulator.
[0073] The chitosan quaternary ammonium salt is hydroxypropyl trimethyl ammonium chloride chitosan, the silane coupling agent is silane coupling agent KH-560, the layered montmorillonite is coconut quaternary ammonium salt modified layered montmorillonite, the dispersant includes sodium polyacrylate and polysorbate 80, and the pH value regulator is a citric acid-sodium citrate buffer system.
[0074] The preparation method of the coconut quaternary ammonium salt modified layered montmorillonite includes the following steps: Q1, 5 g of layered sodium-based montmorillonite is dispersed in 200 mL of deionized water, ultrasonic treated (power 300 W, 30 min) until fully expanded, and then left to stand for 2 hours to remove suspended impurities. After filtration, the purified montmorillonite is dried at 80℃ for 12 hours. The cation exchange capacity of the layered sodium-based montmorillonite is 80-120 mmol / 100 g, and the particle size is more than 200 mesh. Q2, 2.5 g of coconut trimethyl ammonium chloride is dissolved in 50 mL of hot water at 60℃, and stirred until transparent. Q3, add purified montmorillonite into 1.5 L deionized water, ultrasonic dispersion for 30 minutes to form a suspension, adjust the pH to 6-7, slowly add the solution of coconut-based quaternary ammonium salt, react at 60°C under mechanical stirring at 300 rpm for 4 hours, keep the pH stable. The amount of quaternary ammonium salt: the cation exchange capacity of layered sodium montmorillonite = 1.5:1, when the cation exchange capacity of layered sodium montmorillonite is 100 mmol / 100 g, 1.5 g of quaternary ammonium salt is added per 1 g of layered sodium montmorillonite.
[0075] Q4, collect the precipitate by centrifugation (5000 rpm, 10 min), wash 3 times with a volume ratio of 1:1 ethanol-water solution to remove free quaternary ammonium salt. 60°C vacuum drying for 24h, grinding through 200 mesh screen to get coconut-based quaternary ammonium salt modified layered montmorillonite.
[0076] The spray angle of the wide-angle solid nozzle 3 is 120°, and the droplet size range is 50-200 μm.
[0077] The installation height of the wide-angle solid nozzle 3 is 0.5-1.5 m away from the dust source, and the spray coverage area is ≥2 m².
[0078] The three-dimensional network structure has pores with a pore size of 5-10 μm.
[0079] The preparation method of the dust suppressant solution comprises the following steps, S1, after mixing layered montmorillonite with part of the dispersant, mix and stir with modified xanthan gum to obtain a first mixed solution; Add weighed polysorbate 80 in deionized water, stir for 5 minutes until completely dissolved, slowly add coconut-based quaternary ammonium salt modified montmorillonite, increase the stirring speed to 500 rpm for 20 minutes, slowly add modified xanthan gum to avoid agglomeration, reduce the stirring speed to 300 rpm for 30 minutes, until the solution is slightly viscous; S2, dissolve ι-carrageenan in deionized water, stir for 10 minutes until dissolved, slowly drop into the first mixed solution, stir at 300 rpm for 20 minutes, dissolve silane coupling agent KH560 in anhydrous ethanol, slowly drop into the first mixed solution containing carrageenan, stir at 300 rpm for 20 minutes to obtain a second mixed solution.
[0080] S3, dissolve sodium polyacrylate in deionized water, stir for 10 minutes until transparent, slowly add the second mixed solution, stir at 300 rpm for 20 minutes, dissolve hydroxypropyltrimethylammonium chloride chitosan in deionized water, slowly add to the second mixed solution of sodium polyacrylate, stir at 300 rpm for 30 minutes to obtain a third mixed solution; S4, add alkylphenol polyoxyethylene ether to the third mixed solution, adjust the pH to 6.5-8.0, add deionized water and stir uniformly to obtain a dust suppressant solution.
[0081] Dissolve alkylphenol polyoxyethylene ether OP-10 in deionized water, stir for 5 minutes to transparent, add to the third mixture, 300 rpm stirring for 20 minutes. Slowly add citric acid or sodium citrate, monitor pH to 6.5-8.0 with pH meter, 300 rpm stirring for 15 minutes, make up deionized water to 1000 mL total volume, 500 rpm stirring for 10 minutes, after monitoring pH value with pH meter, stand for 30 minutes to remove bubbles, to obtain dust suppressant solution.
[0082] Table 1, orthogonal experiment table
[0083] Table 2, orthogonal experiment results of composite coal dust suppressant
[0084] Configuration method: take 100g as the base, calculate the mass of alkylphenol polyoxyethylene ether, xanthan gum, the mass of the first auxiliary including chitosan quaternary ammonium salt, silane coupling agent, layered montmorillonite, and the mass of the second auxiliary including carrageenan, dispersant, pH value regulator.
[0085] Specifically, appropriate water is measured, and alkylphenol polyoxyethylene ether OP-10 and modified xanthan gum are weighed for orthogonal experimental design of new composite coal dust suppressant.
[0086] The dust suppressant solution is prepared at a temperature range of 20-30℃ and a stirring speed of 300-500r / min to obtain a three-dimensional network structure.
[0087] The orthogonal experiment optimizes the dust suppressant formula through coal sample settlement test and water retention test.
[0088] In the prepared dust suppressant, three concentrations of alkylphenol polyoxyethylene ether OP-10 are contained, with concentrations of 0.02%, 0.05%, and 0.08% respectively, wherein the concentration of 0.02% OP-10 corresponds to 1 of Table 1 orthogonal experiment table, the concentration of 0.05% OP-10 corresponds to 2 of Table 1 orthogonal experiment table, and the concentration of 0.08% OP-10 corresponds to 3 of Table 1 orthogonal experiment table. In the prepared dust suppressant, three concentrations of modified xanthan gum are contained, with concentrations of 0.03%, 0.05%, and 0.07% respectively, wherein the concentration of 0.03% modified xanthan gum corresponds to 1 of Table 1 orthogonal experiment table, the concentration of 0.05% modified xanthan gum corresponds to 2 of Table 1 orthogonal experiment table, and the concentration of 0.07% modified xanthan gum corresponds to 3 of Table 1 orthogonal experiment table.
[0089] Application effect: The scheme A2B2 of Example 5, when the concentration of modified xanthan gum is 0.05%, the concentration of alkylphenol polyoxyethylene ether OP-10 is 0.05%, the coking coal sedimentation time is 42 seconds (pure water > 1 hour), the full dust and dust fall efficiency is 83.82% under the condition of spraying at 1 MPa pressure.
[0090] The scheme A1B2 of Example 2, when the concentration of modified xanthan gum is 0.05%, the concentration of alkylphenol polyoxyethylene ether OP-10 is 0.03%: the dust fall efficiency is 78.5%.
[0091] The scheme A2B1 of Example 4, when the concentration of modified xanthan gum is 0.03%, the concentration of alkylphenol polyoxyethylene ether OP-10 is 0.05%: the water retention is decreased by about 15% compared with the scheme A2B2 of Example 5.
[0092] The scheme A3B1 of Example 7, when the concentration of modified xanthan gum is 0.03%, the concentration of alkylphenol polyoxyethylene ether OP-10 is 0.08%: the dust fall efficiency reaches 91.25% compared with the scheme A2B2 of Example 5, however, the viscosity is decreased by 18.17% in the 7-day storage stability.
[0093] The scheme A3B2 of Example 8, when the concentration of modified xanthan gum is 0.05%, the concentration of alkylphenol polyoxyethylene ether OP-10 is 0.08%: the dust fall efficiency reaches 87.62% compared with the scheme A2B2 of Example 5, however, the viscosity is decreased by 14.41% in the 7-day storage stability.
[0094] In addition, in Tables 3-8, the concentration ranges of the first auxiliary agent include: hydroxypropyltrimethylammonium chloride chitosan 0.01%, silane coupling agent KH-560 0.01%, coconut quaternary ammonium salt modified layered montmorillonite 0.005%, and the concentration ranges of the second auxiliary agent include: i-carrageenan 0.015%, dispersant sodium polyacrylate 0.003%, polysorbate 80 0.002%, and pH value regulator 0.005%. The dust suppressant solution prepared by the above preparation method forms a stable three-dimensional network structure in the solution.
[0095] Table 3, surface tension experiment results
[0096] Table 4, contact angle experiment results
[0097] Table 5, sedimentation experiment results
[0098] Table 6, pH test results
[0099] Table 7, Anti-erosion experiment results
[0100] Table 8, Storage stability experiment results
[0101] As can be seen from Tables 3 to 8, in the case of significant reduction of surface tension by alkylphenol polyoxyethylene ether OP-10, the water retention is poor, the water evaporation speed is fast, leading to easy secondary dust raising, the addition of modified xanthan gum mainly enhances the viscoelasticity of the system, and has little effect on further reduction of surface tension. The modified xanthan gum contains hydrophobic groups and metal ion crosslinking, which mainly increases the solution viscosity through the stretching of molecular chains and network structure, and has weak ability to reduce surface tension. The hydrophobic groups can be adsorbed on the gas-liquid interface, but due to the low concentration of modified xanthan gum, its contribution to surface tension is limited. Tween 80 in the second additive can further reduce the surface tension, so the surface tension value can be further reduced. The pH value of 0.05% alkylphenol polyoxyethylene ether + 0.05% modified xanthan gum + 0.025% first additive + 0.025% second additive is stable between 6.5-8.0, the contact angle with coking coal and long flame coal is lower, the settling time is shorter, and the anti-erosion effect is better.
[0102] In Table 8, 0.05% alkylphenol polyoxyethylene ether has low viscosity, no obvious stratification and no precipitation during standing, and the viscosity retention rate is close to 100%. 0.05% modified xanthan gum has slight stratification and no obvious precipitation due to micelle aggregation during long-term storage, and has good stability. The addition of non-ionic surfactant alkylphenol polyoxyethylene ether in 0.05% alkylphenol polyoxyethylene ether + 0.05% modified xanthan gum reduces the overall viscosity, although the hydrophobicity synergistically enhances the stability, but the dispersibility is insufficient and cannot inhibit the slight stratification of micelle aggregation, leading to increased flocculation and decreased viscosity. In 0.05% alkylphenol polyoxyethylene ether + 0.05% modified xanthan gum + 0.025% first additive + 0.025% second additive, carrageenan can increase the overall viscosity, and the dispersant can reduce the slight stratification of micelle aggregation, so the storage stability is better than that of 0.05% alkylphenol polyoxyethylene ether + 0.05% modified xanthan gum.
[0103] In the present application, after spraying water on the surface of coal, the water on the surface of coal is surface adsorbed water and capillary water, and an air film is formed between the water and the coal. Because the coal is hydrophobic, the water and the coal do not adhere to each other. Therefore, the sprayed water evaporates quickly, and the dust suppression effect disappears quickly. Spraying the composite dust suppressant on the surface of coal ensures the wettability, permeability and adhesion between coal particles. Part of the effective components contained in the composite dust suppressant is used to wet the coal, and the other part is agglomerated to form a three-dimensional network structure, and penetrates and fills the voids of the coal powder particles to form a solidified layer with close arrangement. Xanthan gum reduces the interfacial tension while retaining the good water retention of polysaccharides. Therefore, the composite dust suppressant can solidify the coal powder and enhance the particle agglomeration. In addition, the presence of xanthan gum allows the solidified layer to retain a certain amount of moisture, thereby preventing the cracking of the dry solidified layer, reducing the evaporation rate of moisture, and enhancing the dust suppression effect.
[0104] The present application improves the wettability, adhesion, coagulation and other properties of water by adding materials to water to change the spraying medium, develops a composite dust suppressant capable of forming a three-dimensional network structure, and provides a composite dust suppressant spraying system that synergistically improves the wettability, water retention and wind erosion resistance, thereby improving the efficiency of coal mine spraying dust suppression and solving the problem of secondary dust.
[0105] The above only further illustrates the technical content of the present application by way of examples, so as to make the reader easier to understand, but does not represent that the embodiments of the present application are limited to this, any technical extension or re-creation made according to the present application is protected by the present application. The protection scope of the present application is subject to the claims.
Claims
1. A composite coal dust suppressant spray system characterized by: The dust suppressant solution comprises alkylphenol polyoxyethylene ether and xanthan gum, and has a three-dimensional network structure for filling gaps of coal dust particles.
2. The composite coal dust suppressant spraying system according to claim 1, characterized in that: The wide-angle solid nozzle (3) has a hole diameter of 1.5 mm and a working pressure range of 0.5-1.5 MPa.
3. The composite coal dust suppressant spraying system according to claim 2, characterized in that: The high-pressure water pump (2) is connected to the wide-angle solid nozzle (3) through a water delivery pipeline (4), and the working pressure is 1 MPa.
4. The composite coal dust suppressant spraying system according to claim 1, characterized in that: The concentration of alkylphenol polyoxyethylene ether ranges from 0.02% to 0.08%, and the concentration of xanthan gum ranges from 0.03% to 0.07%. The xanthan gum is a modified xanthan gum with long-chain alkyl hydrophobic groups and metal ions.
5. The composite coal dust suppressant spraying system according to claim 1, characterized in that: The dust suppressant solution further comprises a first additive for improving dust reduction efficiency and a second additive for improving solution stability. The concentration of the first additive ranges from 0.01% to 0.05%, and the concentration of the second additive ranges from 0.01% to 0.05%. The first additive comprises chitosan quaternary ammonium salt, silane coupling agent, and layered montmorillonite, and the second additive comprises carrageenan, dispersant, and pH adjuster.
6. The composite coal dust suppressant spraying system according to claim 1, characterized in that: The wide-angle solid nozzle (3) has a spray angle of 120° and a droplet size range of 50-200 μm.
7. The composite coal dust suppressant spraying system according to claim 1, characterized in that: The installation height of the wide-angle solid nozzle (3) is 0.5-1.5 m away from the dust source, and the spray coverage area is ≥2 m².
8. The composite coal dust suppressant spraying system according to claim 1, characterized in that: The three-dimensional network structure has pores with a hole diameter of 5-10 μm.
9. The composite coal dust suppressant spraying system according to claim 5, characterized in that: The dust suppressant solution is prepared at a temperature range of 20-30°C and a stirring speed of 300-500 r / min to obtain the three-dimensional network structure. The preparation method of the dust suppressant solution comprises the following steps: S1, mixing layered montmorillonite with part of the dispersant, then mixing and stirring with the modified xanthan gum to obtain a first mixed solution; S2, adding carrageenan to the first mixed solution and stirring, then adding and stirring the silane coupling agent to obtain a second mixed solution; S3, adding the remaining dispersant to the second mixed solution, then adding and stirring the chitosan quaternary ammonium salt to obtain a third mixed solution; S4, adding alkylphenol polyoxyethylene ether to the third mixed solution, adjusting the pH to 6.5-7.5, adding deionized water, and stirring uniformly to obtain the dust suppressant solution.
10. Use of a composite coal dust suppressant spray system, characterized in that: The system is applied to coal mine dust reduction.
Citation Information
Cited By
Dust wetting agent for reducing coal mine dust and preparation method thereof
CN121628575A
